ANALYSIS OF THE READINESS OF EDUCATION STUDY PROGRAM STUDENTS TO BECOME PRE-SERVICE TEACHER BASED ON TEACHER COMPETENCY STANDARDS - Fajrul Wahdi Ginting; Agus Muliaman; Isna Rezkia Lukman; Mellyzar Mellyzar (Universitas Negeri Medan, 2020)
The purpose of this study was to describe the self-readiness of students at the Malikussaleh University Education Study Program in Aceh to become professional pre-service teacher based on teacher competency standards after taking microteaching courses. The type of study is descriptive qualitative with the research subjects being student pre-service teacher at the Malikussaleh University Education Study Program who have taken microteaching courses. Data collection techniques through distributing questionnaires or questionnaires to research subjects. The questionnaire consists of an assessment of the professional competence of prospective teachers, an assessment of pedagogical competence, an assessment of social competence, and an assessment of personality. Based on the data obtained and the results of the research analysis, it can be concluded that for the assessment of the professional competence of prospective teachers, students are in the category of very good, good, and sufficient overall were 87% or 136 students. Even so, there are still 13% or 20 students who have not met the competency standards of professional pre-service teacher. In the pedagogical competency assessment, it was found that students in the very good, good, and sufficient categories were 89% or 139 students overall. And it was found that 11% or 17 students had not yet achieved general pedagogical competence. Based on social competence and personality competence, all students achieve the appropriate competence as a professional pre-service teacher.